Экономическая теория: учебник - Бродская Т. Г. Татьяна Григорьевна; Видяпин В. И. Виталий Иванович; Громыко В. В. Валентина Викторовна; Журавлева Г. П. Галина Петровна; Данько Т. П. Тамара Петровна (Москва, Инфра-М, 2008)
100 лет РЭА им. Г. В. Плеханова.